2011
DOI: 10.1136/vr.c6879
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of feline blood for transfusion purposes in the Dublin area of Ireland

Abstract: The prevalence of A, B and AB blood types and of feline immunodeficiency virus (FIV) and feline leukaemia virus (FeLV) infection was determined in cats in Ireland, in order to determine risk factors for blood taken for transfusion purposes. EDTA blood samples were available from 137 non-pedigree cats and 39 pedigree cats (91 females and 85 males, aged four months to 15.0 years) in the Dublin area of Ireland. Of the 176 EDTA blood samples obtained, 112 (from 92 healthy cats and 20 sick cats) were tested for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 30 publications
4
22
1
1
Order By: Relevance
“…) but in agreement with more recent studies (Juvet et al . , Fosset & Blais ), blood type B was more commonly found in domestic rather than purebred cats in the present study. Blood type did not seem to affect short‐term outcome or the occurrence of transfusion‐related complications.…”
Section: Discussionsupporting
confidence: 51%
“…) but in agreement with more recent studies (Juvet et al . , Fosset & Blais ), blood type B was more commonly found in domestic rather than purebred cats in the present study. Blood type did not seem to affect short‐term outcome or the occurrence of transfusion‐related complications.…”
Section: Discussionsupporting
confidence: 51%
“…In this study we have not reported on Mik red cell antigen blood type as there is no commercial test to test this feline blood type [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo observou-se um predomínio do tipo sanguíneo A corroborando os estudos conduzidos com gatos domésticos no Brasil e na Europa (Giger et al, 1992;Ruiz de Gopegui et al, 2004;Vilar, 2006;Lacerda et al, 2008;Medeiros et al, 2008;Marques et al, 2011;Juvet et al, 2011;Mendes et al, 2013;Pinto et al, 2016) como pode ser constatado na Tabela 3. Apesar do predomínio mundial do antígeno eritrocitário A, a frequência varia geograficamente entre 60,9% a 100% (Giger et al, 1992;Mylonakis et al, 2001;Malik et al, 2005;Arikan et al, 2006;Forcada et al, 2007;Zheng et al, 2011;Fosset e Blais, 2014).…”
Section: Methodsunclassified